Corrosion behaviour of Pt-based superalloys intended for high temperature applications. - Maledi, Nthabiseng Beauty (My University, 2008)
ABSTRACT Innovations towards the development of new high temperature alloys led to the development of ternary and quaternary Pt-based superalloys with similar structure to Nibased superalloys (NBSA). These alloys are to be used in the gas turbine industry. This report presents the work that involved aggressive environmental interactions of Pt-based superalloys with molten salt and reducing environments at high temperatures. The work was to serve as materials selection criterion for the developed high temperature alloys. Hot corrosion was conducted at ±950ºC in molten Na2SO4 salt. The controlled mixed gas (0.2%SO2-N2) environment test was performed at 900ºC. Characterisation methods that were used included SEM, Raman, XRD and optical microscopy. The performance of Ptbased superalloys was outstanding, under both test conditions, outperforming the benchmark alloys. Alloy RS1 [Pt-Al-Cr] showed better performance over other investigated Pt-based superalloys and the benchmark alloys in molten salt. Exceptional behaviour was exhibited by alloy RS2 [Pt-Al-Ru] in the mixed gas environment. The uncoated alloy was unable to form a protective oxide scale, which led to the failure of the single crystal alloy. The coated alloy suffered serious degradation under 0.2%SO2-N2 conditions due to the formation of undesirable brittle phases. Ternary Pt-based superalloys are encouraging for further development as the next high temperature alloys in the gas turbine industry.